Dynamic Scattering Approach for Solving the Radar Cross-Section of the Warship under Complex Motion Conditions - Zeyang Zhou; Jun Huang (Photonics, 2020)
To obtain the electromagnetic scattering characteristics of the warship under complex motion conditions, a dynamic scattering approach (DSA) based on physical optics and physical theory of diffraction is presented. The observation angles, turret rotation, hull attitude changes and sea wave models are carefully studied and discussed. The research results show that the pitching and rolling angles have a large effect on the radar cross-section (RCS) of the warship. Turret movement has a greater impact on its own RCS but less impact on the warship. The RCS of the warship varies greatly at various azimuths and elevations. Different sea surface models have a greater impact on the lateral RCS of the warship. The DSA is effective and efficient to study the dynamic RCS of the warship under complex motion conditions.